The New Jewish Diaspora : Russian-speaking Immigrants in the United States, Israel, and Germany - Gitelman, Zvi Y. (Book collections on Project MUSE., 2015)
"Jews of Eastern Europe have immigrated in large numbers to countries like Israel, the United States, and Germany. This migration across international borders has created challenges for Russian-speaking Jews as they forge their cultural, national, and ethnic identities. Gitelman's collection gathers essays on the Russian-speaking Jewish diaspora from scholars in a wide range of fields including sociology, anthropology, literature, political science, history, and demography. By taking a multidisciplinary approach, the volume explores the many issues involving Russian-speaking Jews and their diaspora. Areas of focus include demographically defining the people and the diaspora, and what connects these now separated groups; political attitudes of Russian-speaking Jews and the implications of their convictions; the "malleability" of ethnicity and the process of how identity is recreated when transplanted in a new land; the effects migration has had on religiosity for Russian-speaking Jews; and analyzing the literary voices of writers within the diaspora. No previous volume has dealt in such depth with the ever-growing population of migrant Russian-speaking Jews"--